2008
DOI: 10.1021/jo801470u
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of Allosecurinine and Viroallosecurinine from Menisdaurilide

Abstract: A new and versatile synthetic route to Securinega alkaloids is reported. The first synthesis of allosecurinine has been accomplished in seven steps and 40% yield, starting from (+)-menisdaurilide, using a vinylogous Mannich reaction as the key transformation. Similarly, viroallosecurinine has been synthesized from (-)-menisdaurilide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…A key intermediate of the synthesis is the butenolide 74 , which represents the C and D rings in the final natural product and is the tert ‐butyldiphenylsilyl (TBDPS)‐protected form of the natural product (+)‐aquilegiolide. The route to compound 74 was based on related synthetic studies reported in the literature . Initially the synthesis was designed to yield 73 , which had been isolated from F. virosa in 2012 by Wang, Zhang, Ye and co‐workers .…”
Section: The Total Syntheses Of Bubbialidine and Virosaine Amentioning
confidence: 88%
See 4 more Smart Citations
“…A key intermediate of the synthesis is the butenolide 74 , which represents the C and D rings in the final natural product and is the tert ‐butyldiphenylsilyl (TBDPS)‐protected form of the natural product (+)‐aquilegiolide. The route to compound 74 was based on related synthetic studies reported in the literature . Initially the synthesis was designed to yield 73 , which had been isolated from F. virosa in 2012 by Wang, Zhang, Ye and co‐workers .…”
Section: The Total Syntheses Of Bubbialidine and Virosaine Amentioning
confidence: 88%
“…The same group reported another strategy involving a key vinylogous Mannich reaction in 2008 . Their synthesis commenced from the natural product (+)‐menisdaurilide [(+)‐ 63 ], the synthesis of which they had reported previously, and a possible biogenetic relevance of the key transformation was suggested.…”
Section: Total Synthesis Of Securinega Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations